PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA: KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Sari, Juwita; Rokhmi Fuadati, Siti (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2022)
An effective leadership style in managing human resources and supported by employees' understanding of work will affect work behavior as indicated by an increase in individual job satisfaction and the performance of the unit itself, then affect the company's performance. The purpose of this study was to determine the effect of leadership style on job satisfaction, leadership style on performance, job satisfaction on employee performance and the influence of leadership style on performance through the intervening variable job satisfaction. The research instrument is a questionnaire. Samples were taken as many as 100 respondents, employees of the private hospital in Gresik. Sampling using probability sampling technique. Data analysis using Path analysis by Smart PLS 3. The results showed that all 4 (four) hypotheses were proven and significant, leadership style affects job satisfaction, leadership style affects performance, job satisfaction affects employee performance and leadership style affects performance through the intervening variable job satisfaction.